Detection of Leptin and Ghrelin Hormones and the Expression of their Receptors in Iraqi Obese Individuals - Alsaffar, Sura F.; Jumaa, Hind M.; Baqer , Noor N. (Iraqi Journal of Science, 2024)
Obesity is a complex disease and a major worldwide health hazard with adult mortality. Obesity is defined by an increase in the body-mass index of 30 kg m−2 or greater. It belongs to the genetic predisposition and more consumption of high-energy foods and decreased requirement for physical activity in modern society. This study was designed to evaluate leptin and ghrelin hormones levels and the gene expression of leptin and ghrelin receptors in obese individuals. Seventy-five obese (45 females and 30 males) and 25 (15 females and 10 male) normal individuals were admitted to the Obesity Research and Therapeutic Unit at Alkindy College of Medicine/ University of Baghdad. All blood samples were pulled from obese and normal weight individuals. Leptin and ghrelin hormones were evaluated by ELISA technique and leptin and ghrelin receptors expressions were estimated by RT-PCR. Leptin level was lower in obese than normal 2.74±0.14 ng/ml, 3.47± 0.38 ng/ml respectively. While ghrelin level was higher in obese than normal (26.3 ± 0.56 ng/ml, 17.3 ± 0.5 ng/ml respectively). There was a significant decrease in leptin receptor Ob-Rb mRNA expression in obese individuals (P<0.05). Obese individuals had more ghrelin receptor GHS-R mRNA expression than normal people. In conclusion, obese patients were found to have higher ghrelin hormone and GHS-R as well as low leptin and Ob-Rb mRNA expressions.